Virtual reality in social skills training programs for people with schizophrenia: A systematic review and focus group - Oliveira, Catarina (2021)
This study aims to determine the guidelines for the design of a social skills training programme for people with schizophrenia using virtual reality. This article encompasses two studies: Study 1, a systematic review of five articles indexed in the databases B-on, PubMed, Clinical trials and Cochrane Library (2010–2020); Study 2, a focus group of occupational therapists trained in mental health and multimedia professionals, in which they discussed the outline of such a programme.